East Kalimantan Gas System Hydrocarbon Accounting Robustness with Analytic Hierarchy Process (AHP) - Tanzil, Nessa; Prawiraatmadja, Widhyawan; Dalimunthe, Gallang Perdhana (Yayasan Riset dan Pengembangan Intelektual, 2025)
The study evaluates the robustness of a gas settlement method using the Analytical Hierarchy Process (AHP) to systematically prioritize multiple variables in complex multi-seller, multi-product, and multi-buyer conditions, affected by technical, contractual, and regulatory factors. Expert interviews identified critical variables such as inlet volume, Gross Heating Value (GHV), and operational dynamics across upstream, midstream, and downstream process. AHP calculations and Consistency Ratios validated expert judgments, deriving priority weights for each criterion and subcriterion. Testing scenarios revealed gaps in the lowest scoring scenario, leading to a proposed business solution for dynamic monitoring and integration of system disruptions into the settlement model. The study concludes that AHP-based methodologies provide a structured, transparent decision-making framework suited for complex, multi-stakeholder environments in the East Kalimantan System, advocating for continuous improvement and monitoring to maintain alignment with operational conditions.